Building The Character of Pre-Service Teachers through The Learning Model of Problem-Based Analytical Chemistry Lab Work (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This research aims to apply and find out the characteristics of Problem-Based Instrumental Analysis of Chemistry Lab Work Learning Model (IACLLM) which is able to build the characters, improve the conceptual mastery and the ability of problem solving. The research using experimental quasy with 2 student groups of pre service chemistry teachers as the subjects of the research applied the treatment of problem-based IACLLM for the experimental class and lab work learning with standard lab work procedure in control class. Conceptual mastery was measured using essay test; problem solving skills were measured using assessment of problem solving reports, presentation of the results, and kit making products; whereas the emerged characters were observed during the learning process. The result of this research showed that problem-based IACLLM had open-ended problem characteristic, had produced local material kit, and characters were observed in every stage of problem-based learning model. The implementation of the model could improve the spectrometric and electrometric conceptual mastery, the problem solving skills on a very good level and also some characters were developing during learning process, including religious, discipline, honest, curious, creative, critical, cooperative, communicative, independent, and able to appreciate other people’s opinions and achievements, leadership, democracy, and able to be thorough and careful, and hardworking.